Overcoming mental health care barriers for postpartum depression in developing countries: Zuranolone as a game changer - Eeman, Aqsa; Khan, Muhammad Afaq; Ashraf, Hamza; Ashfaq, Haider (Journal of the Pakistan Medical Association, 2025)
Madam, Postpartum depression (PPD) is defined as the depressive episode occurring during pregnancy or within the first four weeks after childbirth—although symptoms may arise much later. PPD has been under-researched and frequently under-diagnosed, especially due to lack of awareness, limited access to mental health care, and insufficient training for healthcare providers in recognizing and diagnosing PPD. According to literature from lower-middle-income countries, the PPD is estimated to affect about one in five women 1. This condition encompasses a wide spectrum of physical and psychological symptoms, including depressed mood, sleep and appetite disturbances, loss of concentration, psychomotor symptoms and suicidal thoughts. The impact extends beyond the mother’s health, as affected women are less likely to breastfeed, attend well-child visits, or complete infant immunisations. Depressed females have a lower likelihood of breastfeeding, attending well-child visits, completing infant immunizations, use of safety devices and the essential caution for the infants' posture during its sleep and active hours also gets neglected. Hence, the severity of the mother’s depression is directly linked to its impact on the child’s health. Although Brexanolone is currently the first line drug in treating PPD, it has many limitations. One of the major problems in prescribing brexanolone is the need for the patient to be admitted to the hospital for careful monitoring. Moreover, its intravenous (IV) administration is impractical for many patients. The cost of its treatment, ranging somewhere between $15,000 to $34,000 per vial, makes it inaccessible to the masses 2. On the other hand, Zuranolone, a neuroactive steroid (NAS), is a positive allosteric modulator for both synaptic and extra synaptic GABAARs, which has been proven to be an alternative treatment choice for treating PPD. It is the second NAS and first oral medication to receive approval from the FDA for adults suffering from PPD 3. It has a higher efficacy than brexanolone as it can be easily administered once daily and is proven to be more GABA A receptor selective with better oral bioavailability 4. A phase 3, double-blind, randomized placebo-controlled trial demonstrated that zuranolone, when taken once daily for two weeks, led to significant improvements in the depressive symptoms 5. Zuranolone was well tolerated and demonstrated safety, with only mild side effects such as nausea, dizziness, and sedation. ---Continue